Spatial Humanities and Contemporary Geographical Approaches - Alvanides, Seraphim (Serafeim); Paulino, Joana Vieira; Bartzokas-Tsiompras, Alexandros (European Journal of Geography, 2025)
This Special Issue of the European Journal of Geography emerges from the engaging conversations and inspiring work shared at the Spatial Humanities 2024 Conference in Bamberg. It brings together nine original contributions spanning historical geography, urban geography, heritage studies, and geography and education. Through GIS, deep mapping, digital archives, and participatory methods, these studies reveal how spatial thinking and geospatial technologies enrich our understanding of places, histories, and human experiences. Together, they highlight the growing value of spatial humanities in bridging disciplines, telling new stories, and reshaping the ways we explore the world.